Recovery of pituitary function following treatment of an unruptured giant cavernous carotid aneurysm using Surpass flow-diverting stents. (8th May 2014) - Tan, Lee A; Sandler, Victoria; Todorova-Koteva, Kristina; Levine, Laurence; Lopes, Demetrius K; Moftakhar, Roham
Abstract : Giant aneurysms arising from the cavernous internal carotid artery (ICA) can mimic pituitary adenomas and may cause pituitary dysfunction due to their mass effect on the pituitary gland. We report a case of a 56-year-old man presenting with impotence, fatigue and panhypopituitarism who was found to have a giant unruptured aneurysm arising from the right cavernous ICA with severe mass effect on the pituitary gland. The patient underwent endovascular treatment of the giant aneurysm using two telescoping Surpass flow-diverting stents. At 6-month follow-up, repeat cerebral angiography showed Raymond grade II occlusion of the aneurysm with a small neck remnant. At the 10-month follow-up the patient showed full recovery of his pituitary function and clinical resolution of impotence and fatigue. This is the first report of occlusion of a giant cavernous carotid aneurysm using next generation Surpass flow-diverting stents leading to complete recovery of pituitary function.